ENHANCEMENT OF FOREST AND PEATLAND GOVERNANCE IN INDONESIA - Santosa, Mas Achmad (UI Scholars Hub, 2016)
Indonesia’s forest is decreasing rapidly, and it is affecting the country’s commitment to curb carbon emission by 29 percent by 2030. Per a report published by GermanWatch in 2016, our country’s Climate Change Performance Index (CCPI) fell three places from 19 to 22 due to inadequate forest protection policy. This research will look into the urgency for the government of Indonesia to draw an agenda to push forward forest andpeatland reform to stop deforestation. Through a comparative analysis, this paper will compare two government regimes: the second term of President SusiloBambangYudhoyono (2010-2014), where REDD+ was used as the catalyst for forest and peatland governance reform; and the first two years of President JokoWidodo (2014-2016), where promising actions to restore and to protect Indonesia’s forest and peatland still need stronger political will and leadership to meet the 29 per cent commitment to curb greenhouse gas emission in 2030.